2017
DOI: 10.18632/oncotarget.21179
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plasma proteins in children of different Mycobacterium tuberculosis infection status using label-free quantitative proteomics

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is an infectious disease found worldwide. Children infected with MTB are more likely to progress to active TB (ATB); however, the molecular mechanism behind this process has long been a mystery. We employed the label-free quantitative proteomic technology to identify and characterize differences in plasma proteins between ATB and latent TB infection (LTBI) in children. To detect differences that are indicative of MTB infection, we first selected pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Most of the previous studies on TB biomarker screening were focused on the differential analysis between active TB and the other pulmonary diseases (COPD, LC, or pneumonia), or between active TB and HC ( Liu et al, 2011 , 2013 , 2014 ; Song et al, 2014 ; Xu et al, 2014 , 2015 ). Only one study has characterized the plasma proteins in children at different M.TB infection stage (active TB and LTBI), and four proteins (XRCC4, PCF11, SEMA4A, and ATP11A) were detected and confirmed between active TB and LTBI using proteomics analysis and followed western blot analysis ( Li et al, 2017 ). However, these four proteins were not detected in our study, possibly because of the considerable difference in immune response between adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on TB biomarker screening were focused on the differential analysis between active TB and the other pulmonary diseases (COPD, LC, or pneumonia), or between active TB and HC ( Liu et al, 2011 , 2013 , 2014 ; Song et al, 2014 ; Xu et al, 2014 , 2015 ). Only one study has characterized the plasma proteins in children at different M.TB infection stage (active TB and LTBI), and four proteins (XRCC4, PCF11, SEMA4A, and ATP11A) were detected and confirmed between active TB and LTBI using proteomics analysis and followed western blot analysis ( Li et al, 2017 ). However, these four proteins were not detected in our study, possibly because of the considerable difference in immune response between adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a quantitative proteomics approach using LC-MS/MS was employed to characterize plasma from 72 children in different test groups (active TB, inflammatory disease control, and healthy control) at a Beijing Children’s Hospital. The study identified 49 proteins in pediatric cases that were differentially expressed between active and latent TB [ 72 ]. One study characterized the plasma proteins in children at different MTB infection stages (active TB and LTBI), and identified four proteins—XRCC4, PCF11, SEMA4A, and ATP11A—to be signatures of active TB disease using proteomics [ 72 ].…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentmentioning
confidence: 99%
“…The study identified 49 proteins in pediatric cases that were differentially expressed between active and latent TB [ 72 ]. One study characterized the plasma proteins in children at different MTB infection stages (active TB and LTBI), and identified four proteins—XRCC4, PCF11, SEMA4A, and ATP11A—to be signatures of active TB disease using proteomics [ 72 ]. Given the differential presentation of pediatric TB disease, it is likely that a combinatorial approach exploring varied biomarker signature profiles may provide a greater reliability of identification rather than a single factor approach [ 110 ].…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has been widely used in identifying potential biomarkers of cancers, neurodegenerative diseases, renal transplantation, and endocrine system and metabolic diseases . Moreover, the label‐free proteomics technique has also been a promising method to discover TB‐associated protein markers in recent years . However, no study has used this technique to identify potential biomarkers for distinguishing TBPE from MPE, and no study has established a useful diagnostic model for distinguishing TBPE from MPE and further validated it in an independent blind testing set.…”
Section: Introductionmentioning
confidence: 99%